"Clinical Aspects of Chronic Granulomatous Disease in Upper Egypt". (17th February 2021) - El-Mokhtar, Mohamed A.; Salama, Eman H.; Fahmy, Eman Mohamed; Mohamed, Mona Embarek
ABSTRACT: Chronic granulomatous disease (CGD) is a rare inherited primary immunodeficiency disorder that affects phagocytes and is characterized by a marked increased susceptibility to severe bacterial and fungal infections. We aimed to describe the clinical presentations of pediatric patients with CGD in Upper Egypt and to identify the defective component of NADPH oxidase. Pediatric patients diagnosed with CGD within one year from January 2018 to January 2019 were enrolled in the study. Patient history, clinical and laboratory investigations were carried out, including nitroblue tetrazolium test and flow cytometry DHR analysis. Infectious microorganisms were isolated from infected sites to identify the causative agents and their resistance profile. A total of 15 patients were diagnosed with CGD. Failure to thrive and lymphadenopathy were the most common presentations. The median age of clinical onset was 1.17 years of age. The most common gene mutations were observed in the CYBA gene. All cases showed pulmonary infections followed by abscesses. Staphylococcus aureus and Klebsiella pneumoniae were the most frequently isolated bacterial pathogens, Aspergillus spp and Candida spp were isolated from fungal infections. 4/15 (26.7%) children died due to severe serious infections. We concluded that CGD is common in Upper Egypt, and we recommend raising the awareness and testing for CGD in pediatric patients with recurrent or persistent infections, especially those with a familiar history of similar manifestations to avoid delays in proper diagnosis and deterioration of cases. Abbreviations : CGD: chronic granulomatous disease; XL: X-linked; AR: autosomal recessive